Gasification of nickel-loaded oil palm mesocarp fiber for the production of clean syngas / Siti Nor Izuera Nor Azemi - Nor Azemi, Siti Nor Izuera (2015)
This research experimentally investigates the air gasification of nickel-loaded oil palm mesocarp fiber (OPMF) as a low environmental impact catalytic approach to produce clean syngas. The biomass gasification approach used in this study simplifies the catalyst preparation steps and eliminates the use o f additional support materials. In this research, nickel was added directly onto OPMF by soaking with nickel nitrate anhydrate solution, with different initial nickel concentration, initial nickel pH and soaking time. Then, the nickel loaded and unloaded OPMF being gasified to investigate the difference at temperature 750-900°C. The by-product of this process which is nickel containing char being used as a catalyst in the steam reforming of benzene and toluene at 850°C. The presence of nickel enhanced syngas and reduced tar content in the producer gas with tar yield of 0.2% compared with 0.8% of tar yield from gasification of unloaded OPMF. It is believed that nickel particles attached on OPMF and its char promote the catalytic cracking o f tar on their surface and supply radicals to the gas phase to enhance the radical-driven gas-phase reactions for the reforming o f high molecular weight hydrocarbons. The unconsumed nickel-containing char shows great potential to be re-utilised as a catalyst to further enhance tar destruction in the secondary tar reduction process by showing higher composition of CO and H2 compared with the unloaded OPMF char. Overall, this research shows the potential o f using the abundantly available oil palm waste as a renewable energy sources in the gasification process.